Analysis of Self Efficacy on Psychological Stress of Handball Athletes - Sadira Susilawati; Komarudin; Mochamad Yamin Saputra; Geraldi Novian (Universitas Negeri Semarang, 2025)
This study aims to determine how the psychological levels of stress and self-efficacy of handball athletes relate to each other. In addition, this study also seeks components that can increase self-efficacy to reduce stress experienced by athletes. This research method uses a quantitative descriptive correlational research design. Data were collected through a questionnaire consisting of a self-efficacy scale and a psychological stress scale that has been tested for validity and reliability. Respondents in this study were 20 handball athletes who actively competed in West Java Province. The results showed a significant negative relationship between self-efficacy and psychological stress in handball athletes (p < 0.05). Athletes with high self-efficacy tended to have lower levels of psychological stress, while athletes with low self-efficacy experienced higher stress levels. Factors such as competitive experience, social support, and coping strategies also contribute to athletes' self-efficacy levels. Self-efficacy plays an important role in reducing psychological stress in handball athletes. Athletes who are more confident in their abilities tend to be better able to manage stress in sports. Therefore, increasing self-efficacy can be an effective strategy for maintaining mental health and athlete performance.